Implementasi Instrumentasi pada Sistem Deteksi Kebakaran Rumah Berbasis IoT - Ridwan Taufik; Insani Abdi Bangsa; Ulinnuha Latifa (Jurnal Ilmiah Wahana Pendidikan, 2021)
Unpredictable and often uncontrollable catastrophic fires have been growing. The occurrence of fires is very disturbing, damaging, and detrimental to humans both in material and non-material terms. The mistake that often occurs so far is the absence of an early fire extinguisher in the house. As an effort to solve this problem, it is necessary to implement an IoT Based Home Fire Detection System (SIDER) as a fire detector in the house equipped with an automatic extinguishing pump. This research shows the implementation of the DHT22 temperature sensor as a temperature detector, the MQ-135 gas sensor as a smoke detector, and a 5-channel KY-026 fire sensor as a fire detector. The final result of this research is that each sensor has different characteristics. The DHT22 temperature sensor has a sensitivity of 3.1988, and a repetition of 99.51%, the ratio of the temperature value between the sensor and the standard HTC-2 type device which has an error of 0.57%. The MQ-135 gas sensor has a sensitivity value that is generated when there is no smoke, which is 0.01 and a smoke condition is 0.01. The repetability value when it was not there as soon as possible was 79.2% and the current condition was 79.7%. The 5-channel KY-026 fire sensor has a range of 10-60 cm for a candle flame, and a range of 10-10,000 cm for a wood block fire.